URGENSI PELAKSANAAN REHABILITASI BAGI KORBAN PENYALAHGUNANAAN NARKOTIKA DALAM UPAYA MEBERANTASAN TINDAK PIDANA NARKOTIKA - Sofhan, Dedi; Ratnawati, Elfrida (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Narcotics abuse has become a serious problem that affects various levels of society. This investigation aims to find out the need to provide rehabilitation services for narcotics users, understand the rehabilitation process and the consequences of not rehabilitating addicts. So the problem with this research is the negative impact of not providing rehabilitation services to victims of narcotics addiction. This research is called normative because it is intended as a guide to behavior. The research methodology uses a statutory approach and a conceptual approach. The information that has been collected and organized is then assessed qualitatively. The results of this investigation led to the rehabilitation of narcotics addicts. The importance of rehabilitation in overcoming narcotics addiction is very important, because it is difficult for individuals who use narcotics to overcome their addiction, considering that in criminal behavior related to narcotics, both parties are involved. More help is needed for drug abusers. Thus, if someone is sentenced to prison for consuming narcotics, then he will be more likely to be exposed to other crimes because he will have fellow inmates.